Malayalam-English Bilingual Dictionary - (:unkn) unknown (Central Institute of Indian Languages Mysore, 2011)
This is a Malayalam-English bilingual dictionary.
Keywords: Malayalam; Malayalam-English Bilingual Dictionary; Dictionary; Malayalam; Malayalam